2000
DOI: 10.1007/s002230001132
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Trained Young Men Have Higher Calcium Absorption Rates and Plasma Calcitriol Levels Compared with Age-Matched Sedentary Controls

Abstract: The effect of physical activity on human calcium (Ca) metabolism is still not completely understood. Thus, we investigated fractional Ca absorption using a stable strontium test (Fc(240)), calciotropic hormones, and renal Ca excretion in 31 young men with a high activity level (GH) and in 26 age-matched sedentary control subjects (GL). Weekly hours spent on physical activity, obtained with a questionnaire were 15.0 +/- 6.6 (GH) and 1.0 +/- 1.4 (GL), respectively. Serum testosterone levels were significantly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 29 publications
6
27
0
1
Order By: Relevance
“…In well-trained male athletes orally administered with stable strontium as a marker of calcium absorption, Zittermann et al (61) demonstrated increases in the fractional calcium absorption and serum 1,25(OH) 2 D 3 level after a shortterm moderate exercise bout. Another study (60) in male athletes with a minimum of 8 h/wk of endurance sport activities confirmed a 4% increase in the fractional strontium absorption compared with the age-matched sedentary controls. In contrast, immobilization by sciatic denervation in female rats led to a decrease in the duodenal calcium absorption, especially the passive components (58).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In well-trained male athletes orally administered with stable strontium as a marker of calcium absorption, Zittermann et al (61) demonstrated increases in the fractional calcium absorption and serum 1,25(OH) 2 D 3 level after a shortterm moderate exercise bout. Another study (60) in male athletes with a minimum of 8 h/wk of endurance sport activities confirmed a 4% increase in the fractional strontium absorption compared with the age-matched sedentary controls. In contrast, immobilization by sciatic denervation in female rats led to a decrease in the duodenal calcium absorption, especially the passive components (58).…”
Section: Discussionmentioning
confidence: 82%
“…The mechanism of swimming-altered gene expression is currently unknown, but it might be mediated by 1,25(OH) 2 D 3 , as the plasma 1,25(OH) 2 D 3 concentration is typically elevated after endurance exercise (57,58,60). In contrast, immobilization was associated with suppressed 1,25(OH) 2 D 3 synthesis (46).…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Nonsteroidal antiinflammatory drugs (NSAIDs) have been shown to be associated with a reduced risk of colorectal adenomas and cancer in clinical trials 12,13 and might potentially interact with calcium through similar biologic pathways. [14][15][16] Vitamin D and physical activity affect calcium absorption and homeostasis, [17][18][19] which could modify risk, in part, by affecting the amount of free calcium available within the lumen or cells of the colon.…”
mentioning
confidence: 99%
“…Specifični mehanizmi pomoću kojih fizička aktivnost utiče na metabolizam kostiju još uvek nisu potpuno razjašnjeni, međutim, dobro je poznato da povećanje koštane gustine nastaje usled povećanog mehaničkog opterećenja (Frost, 1988), ali izgleda da i ostali parametri, kao što su endokrine promene (Bell et al, 1988;Zittermann et al, 2000;Maimoun et al, 2003), doprinose adaptaciji koštanog sistema. Generalno, mineralna gustina kostiju je od koristi prilikom utvrđivanja snage kostiju i predstavlja primarni indikator rizika nastanka osteoporoze.…”
Section: Kratkoroči I Dugoročni Uticaj Fizičkih Aktivnosti Na Koštaniunclassified